Heparin-induced thrombocytopenia: An Update - Sayami, LA; Ullah, M (Cardiovascular Journal, 2011)
Heparin-induced thrombocytopenia (HIT) is the most important and most frequent drug-induced, immune-mediated type of thrombocytopenia. It is associated with significant morbidity and mortality if unrecognized. In this review, we briefly discuss the main features of heparin-induced thrombocytopenia, particularly analyzing the most recent advances in the pathophysiology, diagnosis and treatment of this syndrome. Keywords: Heparin; Thrombocytopenia DOI: http://dx.doi.org/10.3329/cardio.v3i2.9189 Cardiovasc. J. 2011; 3(2): 187-199